Luminescent solar concentrators employing new Eu(TTA)3phen‐containing parylene films. (3rd July 2014) - Tonezzer, Michele; Maggioni, Gianluigi; Campagnaro, Antonio; Carturan, Sara; Quaranta, Alberto; della Pirriera, Monica; Gutierrez Tauste, David
Abstract New robust luminescent solar concentrators were produced by growing Eu(TTA)3phen‐containing parylene thin films on poly(methyl methacrylate) slabs through a novel co‐deposition process. As it is the first time that Eu(TTA)3phen molecules were inserted in parylene matrix, the deposition process was investigated, and the features of the samples were extensively analyzed. Fourier transform infrared spectroscopy analysis demonstrated the integrity of the vacuum‐sublimated Eu(TTA)3phen molecules. Atomic force microscope analysis showed the very flat surface of the films (Rq = 3.7 nm), which is strategic in luminescent solar concentrators (LSCs) for minimizing the light scattering at the air/film interface. The optical measurements demonstrated that Eu(TTA)3phen‐containing parylene exhibits higher absorption than the conventional Eu(TTA)3phen films and the luminescence peaks characteristic of Eu(TTA)3phen compound. This indicates that the Eu complex is not affected by the matrix interaction thus maintaining its extremely large Stokes shift. Moreover, the parylene matrix improves the luminescence intensity of the films: in fact, under the same absorption, these films show a luminescence intensity more than two times higher than standard Eu(TTA)3phen ones. The current–voltage (I–V) measurements show that, under the same quantity of Eu(TTA)3phen, Eu(TTA)3phen‐containing parylene LSCs produce a current density more than twice as high as LSC without parylene and that their efficiency decreases more than ten times slower than organic‐based LSCs at increasing illuminating area, thus highlighting the feasibility of developing large size LSCs. Copyright © 2014 John Wiley & Sons, Ltd.